ANALYSIS OF THE COMPLETENESS OF FILLING IN ELECTRONIC MEDICAL RESUMES FOR INPATIENTS AT DHARMA YADNYA GENERAL HOSPITAL - Ni Rai Ayu Tunggal Dewi; Ika Setya Purwanti; Made Wahyu Aditya (PT. Jurnal Center Indonesia Publisher, 2025)
People really need health services provided by hospitals, health homes and clinics. When registering for health services, each enrolling member will have his or her own medical history which must be seen at a medical clinic or health office. Hospitals must have comprehensive patient data in order to provide health services effectively. Documents regarding patient identity, examinations, treatment, procedures and other services are included in the medical record. In a health facility, implementation takes the form of an administrative order. Characteristics of medical records (General Patients or BPJS). The aim of this research is to determine the completeness of electronic medical resumes seen from fourth aspects, namely, completeness of identification, important reports, authentication and correct documentation . The method used in this research is quantitative analysis with a descriptive approach. The results of this research are that in the Identification component the percentage of completeness is 100% complete, in the Important Report component the percentage of completeness is 99%, in the Authentication component the percentage of completeness is 100%, and in the Correct Documentation component the percentage of completeness is 90%. Based on the results of research that has been carried out regarding completeness When filling out electronic medical resumes for patients in the Inpatients at RSU Dharma Yadnya, it can be concluded that there are still incompleteness in filling out inpatient electronic medical resumes and that the electronic medical resume components are filled in completely.